2020
DOI: 10.3390/cancers12040859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Urine Fractions for Optimal Bladder Cancer Detection Using DNA Methylation Markers

Abstract: DNA methylation analysis of full void urine and urine pellet seems promising for bladder cancer (BC) detection and surveillance. Urinary cell-free DNA from urine supernatant is now gaining interest for other molecular tests in BC. This study aims to evaluate which urine fraction is preferred for BC diagnosis using methylation markers: full void urine, urine pellet or supernatant. Methylation levels of nine markers were determined in the three urine fractions and correlated with their respective tumor tissues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Different urine fractions showed strong to very strong correlations ( r ≥ 0.77–0.92). Similar findings have been described for the detection of cervical cancer [ 22 , 23 ] and bladder cancer [ 25 ] in different urine fractions. When comparing the AUC values of all fractions, full void urine shows the highest potential for EC detection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Different urine fractions showed strong to very strong correlations ( r ≥ 0.77–0.92). Similar findings have been described for the detection of cervical cancer [ 22 , 23 ] and bladder cancer [ 25 ] in different urine fractions. When comparing the AUC values of all fractions, full void urine shows the highest potential for EC detection.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of DNA methylation markers that hold promise for EC detection have been derived from studies on EC, but also markers developed for cervical cancer detection showed potential diagnostic relevance for EC detection [ 33 ]. We considered the markers GHSR, SST and ZIC1 as interesting candidates to evaluate the detection of EC in the urine by DNA methylation marker testing, based on our previous studies on urinary methylation markers and their diagnostic marker potential for different cancer types [ 22 , 23 , 25 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, miR-935 is a tumor suppressor in non-small cell lung cancer that inhibits E2F7 (40), in gastric signet ring cell carcinoma that inhibits Notch1 (42), and in osteosarcoma that inhibits HMGB1 (43). Moreover, underexpression of miR-935 has also been reported in glioblastoma (44), medulloblastoma (45), uveal melanoma with monosomy-3 (46), 5-FU resistant variants of esophagus SCC (47), non-small cell lung cancer (48), invasive breast cancer cells stably transfected with KLK5 (49), an anoikis resistant variant of the luminal A type breast cancer cells (50), pancreatic cancer (51), bladder cancer (52), colon cancer cell lines with higher potential of metastasis (53), and ovarian cancer (array data of the Gene Expression Omnibus) (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is painful and less sensitive to early diagnosis. On the other hand, some other tests including fluorescence in situ hybridization (FISH) [3], quantitative RT-PCR (RT-qPCR) [4], circulating tumor cells (CTCs) [5], and Im-munoCyt [6] rely on expensive instruments with professional operating, which limits the use of these methods. In addition, other urinary diseases, such as other tumors, urolithiasis, or inflammation, can easily interfere with the results of the above tests [7].…”
Section: Introductionmentioning
confidence: 99%